Carbon nanofiber-RuO2-poly(benzimidazole) ternary hybrids for improved supercapacitor performance - Balan, Beena K.; Chaudhari, Harshal D.; Kharul, Ulhas K.; Kurungot, Sreekumar (RSC Advances, 2013)
Carbon nanofiber-RuO2-poly(benzimidazole) ternary hybrid electrode material which integrates dual wall decoration and interfacial area tuning for supercapacitor applications has been devised based on a simple approach. This is achieved by decorating RuO2 nanoparticles of size ca. 2-3 nm along the inner and outer walls of a hollow carbon nanofiber (CNF) support (F-20RuO(2)). In the next step, a proton conducting polymer, phosphoric acid doped polybenzimidazole (PBI-BuI), interface is created along the inner and outer surfaces of this material. A 103% increase in the specific capacitance is obtained for RuO2-PBI hybrid material as compared to that of F-20RuO(2) at the optimum level of the polymer wrapping. Apart from the high specific capacitance, the RuO2-PBI hybrid materials exhibit enhanced rate capability and excellent electrochemical stability of 98% retention in the capacitance. Such a remarkably high activity can be primarily attributed to the efficient dispersion of active sites achieved by properly utilizing inner and outer surfaces of CNF. Apart from this, the facile routes for ion transport created as a result of PBI incorporation coupled with excellent interfacial contact between the RuO2 and the electrolyte resulting in the improved utilization of the active material also contribute to the improved activity. In addition to this, the synergistic effects of pseudocapacitive contribution from both the PBI-BuI and RuO2 also contribute to the redefined performance characteristics.